The Criminal Offence of Child Maltreatment By Parents in Terms of Child Protection - Rivando Sembiring; Syaiful Asmi Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze and describe the crime of child abuse by parents in terms of child protection aspects. Current developments bring about the evils that society suffers from: violent crimes and maltreatment. One of the most common are crimes involving child victims. Such cases are known as child abuse. Two main problems arise from this declaration. That is, the regulation of criminal sanctions for criminal acts committed by parents and legal protection of children who are abused within the meaning of the Child Protection Act. This investigation uses a normative legal investigation type with a legal and conceptual approach. This research is included in normative research, which is sourced from primary legal materials. Data were collected by using literature and document study methods. The results show that. The imposition of criminal sanctions on criminal acts committed by parents if they meet the elements of Article 76C are child protection against abuse of political activities, involvement in armed conflict, involvement in social unrest, involvement in cases. From Law. Elements of violence, involvement in war and sex crimes.